Knowledge about Dental Caries and The DMF-T Index in Adolescents - Etty Yuniarly; Quroti Ayun; Dewi Erwanti Kumalasari; Dwi Eni Purwati (Dental Therapist Journal, 2024)
Dental caries is one of the most common diseases found in the oral cavity. Based on the 2018 Basic Health Research, 65.5% of 12-year-old children and 67.4% of 15-year-old children experienced caries or cavities, with a national DMF-T index of 7.1. This study aims to determine the level of knowledge about dental caries and the DMF-T index among adolescents. This analytical study used a cross-sectional approach involving 90 randomly selected seventh-grade students. The results showed that 53.3% of respondents had moderate knowledge about dental caries, with an average knowledge score of 8.21. The average DMF-T index was 3.41, with 51.1% of respondents falling into the moderate category. Analysis indicated a tendency for respondents with better knowledge to have a lower DMF-T index. Additionally, 26.7%  of respondents with moderate knowledge had a moderate DMF-T index, suggesting a positive relationship between the level of knowledge and oral health status. The term "moderate" reflects a sufficient but not optimal understanding of oral health and a middle-level degree of tooth decay. Further research is recommended to use longitudinal designs to analyze causal relationships, explore the influence of social factors such as family support, and develop school-based educational programs to enhance awareness and prevent caries among adolescents.